Dr. B. Pattabhi Sitaramayya : a political study - Prasanna Kumar, A. (Sīrīs, 1978)
Study on the life and activities of Bhogaraju Pattabhi Sitaramayya, 1880-1959, a political leader of Karnataka, evaluating his socio-political theories about India.